Digital representations of the real world how to capture, model, and render visual reality - Magnor, Marcus A. (Marcus Andreas) 1972-; Grau, Oliver; Sorkine-Hornung, Olga 1981-; Theobalt, Christian (CRC Press, 2015)
As much as we need computer graphics to generate artificial images (e.g., alien weapons, talking hamsters), we also need digital models of real-world objects for a variety of applications (e.g., digitized cities for online maps, food for commercials, planes for film stunts, cars for virtual reality). This book presents the state-of-the-art research into how complex, real-world scenes are digitized to create realistic virtual worlds. It covers the entire pipeline from acquisition, data processing, and modeling to content editing, photorealistic rendering, and user interaction.